ATRAKSI INTERPERSONAL PADA KOMUNITAS BEDA AGAMA - Maulidah, Faizul; Molyo, Priyo Dari (Jurnal Nomosleca, 2018)
Abstrack Interpersonal attractions in different religious communities is the way a person presents himself to others in a group in which he has a different religious background. In different religious communities, they have a common interest and interest in something but on the other hand there are differences in the religious background of each individual. The goal to be achieved by the researchers is to know how Interpersonal Attraction communicant in building effective interpersonal communication on the community different religion. Researchers use qualitative methods with interviews and observations as the main data collection method to explore how interpersonal attractions are displayed in building interpersonal communication. The result of this research is to bring out the different kinds of communication attraction of other religions: open attitude, empathy, common interest, t growth due to togetherness, physical attractiveness and openness. Keywords: Attractions, Interpersonal Communication and Community Different Religion.DOI :Â https://doi.org/10.26905/nomosleca.v4i1.2051